Meningkatkan Kemampuan Manajemen Keuangan Keluarga: Pelatihan pada Warga RT.4/RW.4, Slipi, Palmerah, Jakarta Barat - Hotben Situmorang; M. Nuhudhul Alim; Ade Andrianto Sihombing; Bernardus Wishman Simbora Siregar (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Community service activity (PKM) entitled "Improving Family Financial Management Skills: Training for Residents of RT.4/RW.4, Slipi, Palmerah, West Jakarta" conducted by STIE IGI Jakarta lecturers on March 23, 2023. The purpose of this activity is to provide knowledge and skills about family financial management to families in the RT.4/RW.4 area, Slipi, Palmerah, West Jakarta. The methods used are lectures, discussions, and simulations. The results showed that the participants experienced an increase in understanding and interest in managing family finances, and were able to plan a family budget according to their income and expenses. This activity is very useful for participants in managing family finances effectively and efficiently.